Economic Evaluation of Geothermal Heat Exchanger in El Oued Region - ATALLAH Azzeddine; BEKKOUCHE Ahmed Amine (University of Shahid Hama Lakhdar - El Oued, 2025)
In this work, it conducted an evaluation economic study of a ground air heat exchanger (GAHE) system. The purpose is to study the feasibility of connecting this exchange to buildings. The application was applied to a poultry house in ElOued region as a case study in order to reduce the consumption of polluting fossil energy used for thermal comfort of poultry. The cumulative cost of this experimental geothermal system over 30 years amounted to 2465560Algerian dinars (DZD), divided into maintenance of 60000 DZD and an initial investment in the first year of installing the system, which was estimated 1453000 DZD. It should not forget the electrical cost of the fans, which was 952560 DZD. On the other hand, it found that the carbon emissions resulting from the generation of electrical energy are estimated 130500.72 kgCO2 and the temperature produced by this system is approximately 24.2°C. في هذا العمل، أجريت دراسة اقتصادية تقييمية لنظام مبادل حراري أرضي هوائي (GAHE). والغرض من ذلك هو دراسة جدوى ربط هذا المبادل بالمباني. وقد تم تطبيق التطبيق على حظيرة دواجن في منطقة الوادي كدراسة حالة من أجل تقليل استهلاك الطاقة الأحفورية الملوثة المستخدمة في الراحة الحرارية للدواجن. بلغت التكلفة التراكمية لهذا النظام التجريبي للطاقة الحرارية الأرضية على مدى 03 عامًا 2465560 دينار جزائري )دج(، مقسمة إلى صيانة قدرها 03333 دج واستثمار أولي في السنة الأولى من تركيب النظام، والذي قُدّر ب 0000333 دج . ويجب ألا ننسى التكلفة الكهربائية للمراوح، والتي بلغت 005003 دج . من ناحية أخرى، وجد أن انبعاثات الكربون الناتجة عن توليد الطاقة الكهربائية تُقدر ب 003033.35 كغ من ثاني أكسيد الكربون، وأن درجة الحرارة التي ينتجها هذا النظام تبلغ حوالي 50.5 درجة مئوية.
Master's thesis specializing in energy.2025
Keywords: GAHE; Experimental; Geothermal energy; System cost; Economic; AHE ؛ تجريبي؛ الطاقة الحرارية الأرضية؛ تكلفة النظام؛ اقتصادي